Clinical-Scale Rapid Autologous BK Virus-Specific T Cell Line Generation From Kidney Transplant Recipients With Active Viremia for Adoptive Immunotherapy. Issue 11 (November 2017) - Lamarche, Caroline; Orio, Julie; Georges-Tobar, Victoria; Pincez, Thomas; Goupil, Mathieu; Dahmani, Amina; Carli, Cedric; Brasey, Ann; Busque, Lambert; Delisle, Jean-Sébastien
Abstract : Background: Polyomavirus-associated nephropathy (PVAN) after BK virus reactivation in kidney transplant recipients (KTR) can compromise graft survival. Lowering immunosuppression is the only established approach to prevent or treat PVAN but nonspecifically increasing host immune competence also augments rejection risk. Ex vivo T cell stimulation/expansion offers the possibility to generate BK-specific T cell lines for adoptive immunotherapy. The objective of this study was to develop and characterize a clinical-scale protocol to generate BK-specific T cell lines from viremic KTR. Methods: Peripheral blood mononuclear cells from healthy controls and viremic KTR were stimulated using BK virus peptide libraries loaded or not on monocytes-derived dendritic cells. Cell counts, flow cytometry, and next-generation sequencing were used to assess T cell expansion, differentiation, and clonal diversity. Enzyme-linked immunospots, cytotoxicity assays as well as adoptive transfer in NOD/SCID/IL2Rγ null mice were used to assess for pathogen-specificity and evidence of nonspecific alloreactivity. Results: T cell lines from KTR and healthy control showed similar characteristics, implying that ongoing immunosuppression and chronic virus exposure do not compromise the differentiation, specificity, or clonal diversity of T cell lines after ex vivo production. Using antigen-loaded dendritic cells improved T cell expansion and favored central memory T cell differentiation. The T cell lines were antigen-specific and showed no nonspecific alloreactivity in vitro and in vivo. Conclusions: Using a rapid, clinically compliant culture system, we show that autologous BK virus-specific T cell lines can be reliably generated from viremic KTR. Our results pave the way for the treatment or prevention of PVAN with adoptive immunotherapy. Abstract : Autologous BK virus-specific T cell lines can be generated from healthy volunteers and viremic kidney transplanted patients using peptide libraries and monocyte-derived dendritic cells. Expanded T cells are central memory, cytotoxic against BK targets and do not recognize xenoantigens in NSG mice. Supplemental digital content is available in the text.